Comparison of Basic Concepts Between Conventional Banks and Sharia Banks - Nisa, Khoirrun (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Conventional banks and Islamic banks are two banking systems that have different principles and mechanisms. This article discusses a basic conceptual comparison between the two, with a focus on operational principles, products offered, and socio-economic impact. The research method used is a qualitative approach through literature study. The analysis results show that although both function as financial institutions, fundamental differences in sharia principles and interest are key factors that influence operations and services provided. This article aims to provide a better understanding of both types of banks to help people choose a financial institution that suits their needs. Keywords : Conventional Banks, Sharia Banks, Operational Principles.